CENTRAL ASIA: POLITICAL LEGITIMATION MODELS - TRUEVTSEV, Konstantin (CENTRAL ASIA AND THE CAUCASUS, 2007)
In his book The Grand Failure1 that appeared in 1989, Zbigniew Brzezinski offered two major conclusions: the Soviet Union would inevitably fall apart to be replaced, nearly everywhere, with authoritarian regimes. The democratic euphoria of the time distorted these conclusions in shocking and fantastic inventions. They were not, however, pulled out of thin air: they were products of an analysis of the political processes underway in the Soviet Union.Today, the first statement looks like a banality. The second statement is not as unambiguous The national states that sprang into being on the Soviet Union’s detritus can be divided into several groups.The first includes the countries in which the political opposition prevailed and followed the road of revolutionary changes, which included, among other things, nearly total replacement of the Soviet structures with alternative political constructs. This happened in the Baltic countries and Russia, which acquired, as a result, the most stable political systems and institutions of representative democracy across the post-Soviet expanse.The second group went through a period of revolutionary upheavals much more intensive and much more violent than those that fell to the first group’s lot. The civil, ethnic, and clan wars, however, did not, as a rule, call to life any deep cutting political changes: no Soviet structures were destroyed to make room for political institutions adequate to the current context and the local traditions and mentality. This group, which includes the Transcaucasian countries, Moldova, and Tajikistan, paid for the resultant systemic inadequacy with either political instability (which brought Georgia and Moldova very close to the “failed state” status) or a more or less severe authoritarian system (Azerbaijan and Tajikistan). The third group is of the greatest interest for the purposes of the present article. At first (in the early 1990s), it included Ukraine, Belarus, Kazakhstan, Uzbekistan, and Turkmenistan. Later, however, Ukraine started moving away from this group, but today, in the post Orange Revolution period, it has preserved some of the group’s most important features.2 Later Tajikistan, Azerbaijan, and, partially at least, Kyrgyzstan joined this group.Any description of the group should point to the fact that, as distinct from the first two, this group tends, on the whole, toward an evolutionary model of post-Soviet political development. This is an important, albeit so far superficial, description of this model. To probe deeper into its meaning we should discuss its structural-functional features, including the genetic ones. To do this we must go back to the very beginning.